Quality and quantity of dromedary camel DNA sampled from whole-blood, saliva, and tail-hair - Alhaddad, Hasan (PLoS One, 2019)
Camels are livestock with unique adaptations to hot-arid regions. To effectively study camel traits, a biobank of camel DNA specimens with associated biological information is needed. We examined whole-blood, saliva (buccal swabs), and tail-hair follicle samples to determine which is the best source for establishing a DNA biobank. We inspected five amounts of each of whole-blood, buccal swabs, and tail-hair follicles in nine camels, both qualitatively via gel electrophoresis and quantitatively using a NanoDrop spectrophotometer. We also tested the effects of long term-storage on the quality and quantity of DNA, and measured the rate of degradation, by analyzing three buccal swab samples and 30 tail-hair follicles over a period of nine months. Good quality DNA, in the form of visible large size DNA bands, was extracted from all three sources, for all five amounts. The five volumes of whole-blood samples (20–100μl) provided ~0.4–3.6 μg, the five quantities of buccal swabs (1–5) produced ~0.1–12 μg, while the five amounts of tail-hair follicles (10–50) resulted in ~0.7–25 μg. No differences in the rate of degradation of buccal swab and tail-hair follicle DNA were detected, but there was clearly greater deterioration in the quality of DNA extracted from buccal swabs when compared to tail-hair follicles. We recommend using tail-hair samples for camel DNA biobanking, because it resulted in both an adequate quality and quantity of DNA, along with its ease of collection, transportation, and storage. Compared to its success in studies of other domesticated animals, we anticipate that using ~50 tail-hair follicles will provide sufficient DNA for sequencing or SNP genotyping.